Advanced and Innovative Nano-Systems for Anticancer Targeted Drug Delivery - Lu Tang; Jing Li; Qingqing Zhao; Ting Pan; Hui Zhong; Wei Wang (MDPI AG, 2021)
The encapsulation of therapeutic agents into nano-based drug delivery system for cancer treatment has received considerable attention in recent years. Advancements in nanotechnology provide an opportunity for efficient delivery of anticancer drugs. The unique properties of nanoparticles not only allow cancer-specific drug delivery by inherent passive targeting phenomena and adopting active targeting strategies, but also improve the pharmacokinetics and bioavailability of the loaded drugs, leading to enhanced therapeutic efficacy and safety compared to conventional treatment modalities. Small molecule drugs are the most widely used anticancer agents at present, while biological macromolecules, such as therapeutic antibodies, peptides and genes, have gained increasing attention. Therefore, this review focuses on the recent achievements of novel nano-encapsulation in targeted drug delivery. A comprehensive introduction of intelligent delivery strategies based on various nanocarriers to encapsulate small molecule chemotherapeutic drugs and biological macromolecule drugs in cancer treatment will also be highlighted.